Chir Pine (Pinus roxburghii) and Blue Pine (P. wallichiana) Forests in West Nepal: Comparing Associated Plant Species - Subedi, Chandra Kanta; Rokaya, Maan Bahadur; Gurung, Janita; Timsina, Binu; Bhandari, Prabin; Chaudhary, Ram Prasad (Journal of Institute of Science and Technology, 2022)
Chir pine (Pinus roxburghii) and blue pine (P. wallichiana) are two dominant tree species in the mid-hill forests of Nepal that also contribute significantly to the country’s total forest area. The associated vegetation pattern in pine forests is influenced by environmental and edaphic factors. The objective of this study was to determine the correlation between soil chemical properties and the composition of associated plant species of two pine forests in the Kailash Sacred Landscape, Nepal. We used the quadrat sampling method to collect vegetation and soil data. Pearson’s correlation was used to determine the relationship between soil chemical properties. Generalized Linear model (GLM) to assess the effect of soil properties on species richness, and Canonical Correlation Analysis (CCA) for species composition. Our analysis showed that soil pH was negatively correlated with soil chemical properties and species richness of associated species. There was a high number of associated plant species in the blue pine forest than in chir pine forest. Associated plant species generally prefer high nitrogen and phosphorus content. Between the two pine forest types, there was a higher number of associated plant species in the blue pine forest than in chir pine forest. The study showed that two closely related pine forests differ in associated plant species diversity and richness. Soil nutrients play an important role in determining the species richness and composition but may not be the only factors affecting these patterns. Pine forests play an important role in the socio-economy from the national to community levels while the associated plant species have more significant functions in the livelihoods of local communities.